Manejo de residuos sólidos en pequeñas comunidades del sector rural de Quevedo. - Padilla Baño, Katherine Narcisa (2013)
This research was conducted in the Los Ríos province, specific in Quevedo city, geographical location is 78 ° 30'45 "west longitude and 0 ° 13 '23" south latitude, at an altitude of 74 meters. The primary objective was to evaluate the management of solid waste in the three rural communities La Virginia No. 2, La Colonia and El Lechugal. For the qualitative and quantitative characterization of solid waste, a preview was held in the communities; we determined the sample size, surrendered containers for collection of waste from organic and inorganic separately, then sorted and weighed the same. Also applied the Likert questionnaire to determine current management effects on human health of the inhabitants. The values of per capita generation of solid waste in rural communities La Virginia No. 2 was 0.64 kg/hab día, La Colonia 0.38 kg/ habdía and Lechugal 0.49 kg/habdía. It was determined that there is no method of final disposal in solid waste management in the three communities, which affects the health of the population. Finally, the proposal raised in improved management of waste with organic waste, making compost in three rural communities; and inorganic wastes in La Virginia No. 2 and El Lechugal is formulated implementing a center recycling in every community in La Colonia is proposed the model of a trench type sanitary landfill.